2018
DOI: 10.1007/s10620-018-5219-9
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at Familial Risk of Inflammatory Bowel Disease in the Ashkenazi Jewish Population

Abstract: Background and AimsThe inflammatory bowel diseases (IBD) are particularly common among the Ashkenazi Jewish (AJ) population. Population-specific estimates of familial risk are important for counseling; however, relatively small cohorts of AJ IBD patients have been analyzed for familial risk to date. This study aimed to recruit a new cohort of AJ IBD patients, mainly from the UK, to determine the familial occurrence of disease.MethodsA total of 864 AJ IBD patients were recruited through advertisements, hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…3a). As reported in [11], [37], [38], we find that Ashkenazi Jews are more likely to be assigned phecodes for ulcerative colitis (log odds ratio: 0.81±0.2, p-value: 6.61e-15), chronic ulcerative colitis (log odds ratio: 0.74±0.23, p-value: 6.88e-10) and regional enteritis (log odds ratio: 1.08±0.20, p-value: 4.23e-27). We additionally observed strong associations for several mental health disorders, including obsessive-compulsive disorder (log odds ratio: 1.13±0.33, p-value: 2.49e-11), eating disorder (log odds ratio: 1.22±0.32, p-value: 1.02e-13), anxiety disorder (log odds ratio: 0.53±0.07, p-value: 8.75e-55), and major depressive disorder (log odds ratio: 0.48±0.1, p-value: 9.02e-23).…”
Section: Phecodessupporting
confidence: 67%
“…3a). As reported in [11], [37], [38], we find that Ashkenazi Jews are more likely to be assigned phecodes for ulcerative colitis (log odds ratio: 0.81±0.2, p-value: 6.61e-15), chronic ulcerative colitis (log odds ratio: 0.74±0.23, p-value: 6.88e-10) and regional enteritis (log odds ratio: 1.08±0.20, p-value: 4.23e-27). We additionally observed strong associations for several mental health disorders, including obsessive-compulsive disorder (log odds ratio: 1.13±0.33, p-value: 2.49e-11), eating disorder (log odds ratio: 1.22±0.32, p-value: 1.02e-13), anxiety disorder (log odds ratio: 0.53±0.07, p-value: 8.75e-55), and major depressive disorder (log odds ratio: 0.48±0.1, p-value: 9.02e-23).…”
Section: Phecodessupporting
confidence: 67%
“…The rate may be even higher in the Jewish population, that comprises the vast majority of our cohort [6]. In 2018, Schiff et al [22] reported a 40% rate of familial cases of IBD in the Ashkenazi Jewish population in the UK. That high rate may re ect a greater genetic burden for IBD among that population compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the prevalence of inflammatory bowel disease in patients with HPS was higher than in the general population and in comparable ethnic groups. For example, inflammatory bowel disease is estimated to affect more than 0.3% of the general North American population and 1.2% of the Ashkenazi Jewish population [49,50]. In addition, the prevalence of Crohn's disease and inflammatory bowel disease in Puerto…”
Section: Discussionmentioning
confidence: 99%